The Influence of Product Quality, Member Satisfaction, and Brand Image on Member Loyalty of the Baitul Tamwil Muhammadiyah Mulia Sharia Consumer Cooperative - Alfain Jalaluddin Ramadlan; Farokhah Muzayinatun Niswah; Dita Pratiwi Kusumaningtyas; Elvina Assadam (Journal of Islamic Economy, 2025)
Competition in the world of the sharia cooperative industry requires administrators to work harder to maintain the loyalty of members so that they do not move to other competitors. So it is important for the management to know the factors that can affect the loyalty of its members. The purpose of this study is to determine the influence of product quality variables, member satisfaction, and brand image on the loyalty of members of the Sharia Consumer Cooperative (KKS) Baitul Tamwil Muhammadiyah (BTM) Mulia partially and simultaneously. The sample used in this study was 98 samples selected by the purposive sampling method with the respondent criteria, namely active members of the KKS BTM Mulia and members who have purchased products or services more than once. The data were processed using multiple linear regression analysis techniques. Based on the test, it was found that member satisfaction and brand image had a positive and significant effect on the loyalty of KKS BTM Mulia members, while product quality had no effect on the loyalty of KKS BTM Mulia members. Product quality, member satisfaction, and brand image simultaneously have a positive and significant effect on the loyalty of KKS BTM Mulia members.